Hubungan Literasi Informasi Digital dengan Sikap Kritis Mahasiswa terhadap Konten Clickbait di Media Sosial - Zain, Muhammad Roofid; Asmara, Rini (AHKAM, 2026)
Although social media has become a primary source of information for students, the proliferation of clickbait content raises concerns about the quality and credibility of the information consumed. However, studies that specifically discuss the relationship between digital information literacy and students’ critical attitudes toward clickbait content remain limited. This study aimed to analyze the relationship between information literacy and students’ critical attitudes toward clickbait content on social media. This study used a quantitative approach with a correlational design, involving 100 respondents selected using purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using Pearson Product Moment correlation. The results showed a significant positive relationship between information literacy and students’ critical attitudes. This finding contributes to the development of studies on information literacy and critical thinking in digital contexts, particularly in dealing with potentially misleading information on social media. Thus, information literacy plays an important role in shaping students’ ability to evaluate, assess, and respond critically to clickbait content.